2022
DOI: 10.3390/ijerph19020733
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Workers Attitudes, Practices and Sources of Information for COVID-19 Vaccination: An Italian National Survey

Abstract: Vaccination of healthcare workers (HCWs) is a crucial element to overcome the COVID-19 pandemic. The aim of this survey was to assess attitudes, sources of information and practices among Italian Healthcare workers (HCWs) in relation to COVID-19 vaccination. Methods: From 19 February to 23 April 2021, an anonymous voluntary questionnaire was sent to the mailing list of the main National Health Service structures. Data were collected through the SurveyMonkey platform. Results: A total of 2137 HCWs answered. Hes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 28 publications
3
33
0
Order By: Relevance
“…A similar pattern was reported in two different studies from Saudi Arabia and Italy [101][102][103]. Taken together, the differences in influenza vaccine acceptance based on HCW category should be taken into account in efforts aimed at increasing vaccine uptake [100].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A similar pattern was reported in two different studies from Saudi Arabia and Italy [101][102][103]. Taken together, the differences in influenza vaccine acceptance based on HCW category should be taken into account in efforts aimed at increasing vaccine uptake [100].…”
Section: Discussionsupporting
confidence: 84%
“…The differences observed in the rates of influenza vaccine acceptance and uptake among HCW categories warrant implementation of slightly different strategies for vaccine promotion depending on the group. These strategies are recommended to be tailored according to occupational category [89,100]. In this study, physicians had the highest rates of vaccine acceptance compared to nurses.…”
Section: Discussionmentioning
confidence: 78%
“…A recent study in the U.S among medical students revealed a link between vaccination knowledge and attitudes toward mandatory COVID-19 vaccination for patients ( 17 ). Furthermore, recent evidence suggests that HCPs with low educational levels are opposed to mandatory COVID-19 vaccination for HCPs ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there was no difference as regard age, gender or working with COVID-19 patients in our cohort. In previous studies, it was observed that males and physicians were more accepting of vaccinations than females and nurses [40] [24] [41]. Because of this, physicians play a signi cant part in increasing public acceptability of the COVID-19 vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians were reported to be primary source of information in about half of our participants (49%) followed by social media for young participants (<45 years) and television for others (≄45 years). It was found that higher education HCWs rely mainly on institutional sources and scienti c literature, however, lower education HCWs rely on internet, mass media and opinions of family and friends [41]. Social and mass media are important sources of information [44].However, using social media as a source of information is associated with more vaccine hesitancy [45], while using national websites is associated with less hesitancy [35].…”
Section: Discussionmentioning
confidence: 99%